Impact of Reduced Dietary Crude Protein in the Starter Phase on Immune Development and Response of Broilers Throughout the Growth Period - Kamely, Mohammad; He, Wanwei; Wakaruk, Jeremy; Whelan, Rose; Naranjo, Victor; Barreda, Daniel R. (Frontiers in Veterinary Science, 2020)
Crude protein (CP) levels in commercial broiler (Gallus gallus) diets, optimized for maximum yield production vs. feed cost, have only begun to be assessed for impact on immune function. In order to study immune effects of dietary CP levels, different starter phase (day 1 to 14) diets were fed to 230 Ross 708 male broiler chicks randomly assigned at 1-day of age into 2 treatment groups. Group 1: Standard diet (STD) contained 3000 kcal AMEn/kg energy and 23.78 % CP and Group 2: Reduced crude protein diet (RCP) contained 3000 kcal AMEn/kg energy and 21.23 % CP. From day 15 to 35 a common standard grower/finisher diet (3150 kcal AMEn/kg energy and 22.18 % CP was allocated to both groups. Zymosan, a glycan derived from yeast cell walls that binds to TLR 2 and Dectin-1, was used for intra-abdominal challenge. Results demonstrated that a reduced crude protein starter diet (21.23 % vs 23.78 % CP) between age 1 to 14, while maintaining the same levels of metabolizable energy and essential amino acids, did not affect broilers growth performance or lymphoid organ weights (P > 0.05). Interestingly, basal leukocyte levels in the RCP group significantly (P < 0.01) increased in the blood compartment at d35 in the unchallenged birds. Significant enhancements to leukocyte infiltration into the abdominal cavity were also detected post-immune challenge with zymosan (day 14 and day 35; P < 0.01). Post-challenge levels of TNF-α, IL-1β and CXCL8 gene expression cells collected from the abdominal cavity were not affected by the diets (P > 0.05). Moreover, dietary treatments did not influence percentage of ROS producing cells in the abdominal cavity (P > 0.05). To our best knowledge, this is the first study that reports the impacts of reduced crude protein diet on the innate immune response of poultry to an acute inflammation model in the abdominal cavity. Overall, our results highlight that reduced crude protein diets can be used without negatively impacting broiler performance and may enhance the capacity of broilers to recruit leukocytes upon infection.